2004
DOI: 10.1136/gut.2004.039032
|View full text |Cite
|
Sign up to set email alerts
|

Testing for faecal calprotectin (PhiCal) in the Norwegian Colorectal Cancer Prevention trial on flexible sigmoidoscopy screening: comparison with an immunochemical test for occult blood (FlexSure OBT)

Abstract: Background: Screening for colorectal cancer (CRC) using guaiac based faecal occult blood tests (FOBT) has an estimated programme sensitivity of .60% but ,30% for strictly asymptomatic CRC in a single screening round. In search for improved non-invasive tests for screening, we compared a test for faecal calprotectin (PhiCal) with a human haemoglobin immunochemical FOBT (FlexSure OBT). Methods: In the Norwegian Colorectal Cancer Prevention (NORCCAP) trial, screenees in one screening arm were offered screening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
2
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 21 publications
2
31
2
2
Order By: Relevance
“…Calprotectin, a stable neutrophil-specific marker, has also been shown to be a simple and sensitive marker of colorectal cancer [19,20]. Information about colonic polyps is scarce, however.…”
Section: Discussionmentioning
confidence: 99%
“…Calprotectin, a stable neutrophil-specific marker, has also been shown to be a simple and sensitive marker of colorectal cancer [19,20]. Information about colonic polyps is scarce, however.…”
Section: Discussionmentioning
confidence: 99%
“…It raises the question whether calprotectin might have a role in colorectal cancer screening. Consideration of that is outwith the scope of this review but we note that Hoff et al 178 from Norway compared calprotectin (PhiCal, Eurospital) with FOBT (using an immunochemical method) and concluded that FOBT was better.…”
Section: Raised Calprotectin In Larger Adenomasmentioning
confidence: 99%
“…Like previous studies of the same design, we did not include patients with GI-associated inflammation or nonmalignant tumors since fecal calprotectin level may increase in these conditions (Summerton et al, 2002;Hoff et al, 2004;Fagerberg et al, 2005). Meanwhile, our findings demonstrated an abnormal distribution of fecal calprotectin level in CRC and gastric cancer patients.…”
Section: Discussionmentioning
confidence: 55%
“…The positive level of fecal calprotectin was considered greater than 50µg/g. As a result, the sensitivity of this marker to distinguish CRC from other conditions was reported 27%, however, when all suspected malignant conditions were considered together the sensitivity reached 76% (Hoff et al, 2004). Other studies reported different sensitivity and specificity values.…”
Section: Discussionmentioning
confidence: 97%